Theoretical Survey on Cadmium Sulfide Thin Films for Solar Cell Applications - Arunraja1, L.; Thirumoorthy2, P.; Dhatchinamurthy1, L. (Asian Journal of Chemistry, 2013)
Cadmium sulfide thin films are one of the most promising materials due to its photo conducting nature and suitable band gap (2.42 eV), It has been used for several types of thin film solar cells. In this paper we present some new investigation made on cadmium sulfide thin films used, we can change the compound as well as the concentration will be changed. The films thickness was in the range (102-120) nm and most film's thickness decreased while Zn concentration in solution increased. The transmittance of films increased as Zn concentration increased. All films, however, have high transmittance of 65-86 % the wavelength region (500-900 nm). This material has many applications and from these applications we are interested in photovoltaic applications.